2014
DOI: 10.4103/2141-9248.133364
|View full text |Cite
|
Sign up to set email alerts
|

Mobile and portable dental services catering to the basic oral health needs of the underserved population in developing countries: A proposed model

Abstract: India is the second most populous country in the world with an extensive rural population (68.8%). Children less than 18 years constitute about 40% of the population. Approximately, 23.5% of the urban population resides in urban slums. The extensive rural population, school children and the urban slum dwellers are denied of even the basic dental services though there is continuous advancement in the field of dentistry. The dentist to population ratio has dramatically improved in the last one to two decades wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 18 publications
(23 reference statements)
0
29
0
Order By: Relevance
“…Ganavadiya et. al [26] has shown that spreading awareness about good dental care practices can have major improvements for underserved populations.…”
Section: Sources Of Innovation and Potential Servicesmentioning
confidence: 99%
“…Ganavadiya et. al [26] has shown that spreading awareness about good dental care practices can have major improvements for underserved populations.…”
Section: Sources Of Innovation and Potential Servicesmentioning
confidence: 99%
“…In India, the distribution of dentists is grossly uneven with more than 90% of dentists available in urban settings and only 10% available for 72% of the rural population. There are no dentists posted at the level of primary and community health centers in most of the area of Madhya Pradesh state [2].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 23.5% of the urban population resides in urban slums. The extensive rural population, school children and the urban slum dwellers are denied of even the basic dental services though there is continuous advancement in the field of dentistry [2]. Typically, the options available for the delivery of services are traditional stationary clinics; portable equipment; or mobile dental clinics (van or truck) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Even if most dental procedures are performed in private practices, mobile dental delivery systems (MDDSs) ( Figure 1) are receiving growing interest in the field of dentistry [1,2]. Many reasons can be attributed to this interest.…”
Section: Introductionmentioning
confidence: 99%